The Influence of Sharia Financial Literacy and Social Environment on the Interest in Saving of College Students in Sharia Banks - Azizah Awaliah; Baiq Anggun Hilendri Lestari (International Economic Conference of Business and Accounting, 2024)
This study aimed to determine the effect of Sharia financial literacy and social environment on the interest in saving of college students in Sharia banks. The population in this study consisted of students from the Faculty of Economics and Business at the University of Mataram. Samples may taken by purposive sampling of 100 respondents who are active students of the Faculty of Economics and Business at the University of Mataram. Data were collected using a questionnaire distributed online via Google Forms. The analytical technique used to test the hypothesis is the multiple regression method, processed with the SmartPLS 4 data processing program. The results show that (1) Sharia financial literacy has a significant effect on the interest in saving of college students in Sharia banks, and (2) the social environment has a significant effect on the interest in saving of college students in Sharia banks.